Children’s letter naming in the year before school enrollment in the context of Croatian language and orthography - Jozipović, Marija; Lenček, Mirjana; Kovačević, Maja (23rd Psychology Days in Zadar: Book of Selected Proceedings, 2024)
Early literacy refers to the skills and abilities essential to the later acquisition of reading that a child acquires before formal instruction begins (Scarborough, 2001). Two groups of factors related to the concept of early literacy are distinguished: language and environmental factors (Kuvač Kraljević et al., 2019). Among language factors, letter knowledge is the single most important predictor of successful reading (Georgiou et al., 2012; Muter & Diethelm, 2001; Torppa et al., 2006), especially in alphabetic languages with transparent orthography like Croatian. Foreign research shows that children at risk of developing reading disorders, i.e., dyslexia know fewer letters than their typically developing peers (Lyytinen et al., 2004; Puolakanaho, 2007). The aim of this study is to describe letter knowledge in Croatian-speaking typically developing and at-risk preschool children. As hypothesized, children at risk named on average fewer upper- and lowercase letters than their typically developing peers. Considering the importance of predictors of reading and the possibility of developing prevention programs in this area, it is important to understand the meaning, contexts and development of pre-skills in reading and writing.